Photoactivatable Organometallic Pyridyl Ruthenium(II) Arene Complexes - Betanzos-Lara, Soledad; Salassa, Luca; Habtemariam, Abraha; Novakova, Olga; Pizarro, Ana M; Clarkson, Guy J; Liskova, Barbora; Brabec, Viktor; Sadler, Peter J (Organometallics, 2012)
The synthesis and characterization of a family of piano-stool RuII arene complexes of the type [(η6-arene)Ru(N,N′)(L)][PF6]2, where arene is p-cymene (p-cym), hexamethylbenzene (hmb), or indane (ind), N,N′ is 2,2′-bipyrimidine (bpm), 1,10-phenanthroline (phen), 1,10-phenanthroline-5,6-dione (phendio), or 4,7-diphenyl-1,10-phenanthroline (bathophen), and L is pyridine (Py), 4-methylpyridine (4-MePy), 4-methoxypyridine (4-MeOPy), 4,4′-bipyridine (4,4′-bpy), 4-phenylpyridine (4-PhPy), 4-benzylpyridine (4-BzPy), 1,2,4-triazole (trz), 3-acetylpyridine (3-AcPy), nicotinamide (NA), or methyl nicotinate (MN), are reported, including the X-ray crystal structures of [(η6-p-cym)Ru(bpm)(4-MePy)]2+ (2), [(η6-p-cym)Ru(bpm)(4-BzPy)]2+ (6), [(η6-p-cym)Ru(bpm)(trz)]2+ (7), [(η6-p-cym)Ru(phen)(Py)]2+ (10), and [(η6-ind)Ru(bpy)(Py)]2+ (13). These complexes can selectively photodissociate the monodentate ligand (L) when excited with UVA or white light, allowing strict control of the formation of the reactive aqua species [(η6-arene)Ru(N,N′)(OH2)]2+ that otherwise would not form in the dark. The photoproducts were characterized by UV–vis absorption and 1H NMR spectroscopy. DFT and TD-DFT calculations were employed to characterize the excited states and to obtain information on the photochemistry of the complexes. All the RuII pyridine complexes follow a relatively similar photochemical L-ligand dissociation mechanism, likely to occur from a series of 3MC triplet states with dissociative character. The photochemical process proved to be much more efficient when UVA-range irradiation was used. More strikingly, light activation was used to phototrigger binding of these potential anticancer agents with discriminating preference toward 9-ethylguanine (9-EtG) over 9-ethyladenine (9-EtA). Calf thymus (CT)-DNA binding studies showed that the irradiated complexes bind to CT-DNA, whereas the nonirradiated forms bind negligibly. Studies of CT-DNA interactions in cell-free media suggest combined weak monofunctional coordinative and intercalative binding modes. The RuII arene complexes [(η6-p-cym)Ru(bpm)(Py)]2+ (1), [(η6-p-cym)Ru(bpm)(4-MeOPy)]2+ (3), [(η6-p-cym)Ru(4,4′-bpy)]2+ (4), [(η6-hmb)Ru(bpm)(Py)]2+ (8), [(η6-ind)Ru(bpm)(Py)]2+ (9), [(η6-p-cym)Ru(phen)(Py)]2+ (10), [(η6-p-cym)Ru(bathophen)(Py)]2+ (12), [(η6-p-cym)Ru(bpm)(NA)]2+ (15), and [(η6-p-cym)Ru(bpm)(MN)]2+ (16) were cytotoxic toward A2780 human ovarian cancer cell line in the absence of photoirradiation (IC50 values in the range of 9.0–60 μM).